2000
DOI: 10.1002/(sici)1097-4628(20000103)75:1<68::aid-app8>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane/conducting carbon black composites: Structure, electric conductivity, strain recovery behavior, and their relationships

Abstract: The polyurethane composites with conducting carbon black (CB) were prepared by a solution-precipitation process, which was followed by melt compression molding. The polyurethane used has good shape memory effect. The morphology of CB fillers in polyurethane matrix and the resulting conductivity of the composites were investigated. It has been found that CB fillers exist in the forms of aggregates. The percolation threshold is achieved at the CB concentration of 20 wt %. The presence of CB fillers decreases the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…The combination of conventional polymers with conductive polymers or filler allows to create new polymeric materials with unique electrical properties. Li et al [7] prepared conducting shape memory polyurethane incorporating carbon black. They studied the shape memory properties by applying thermal heating but not electrical voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of conventional polymers with conductive polymers or filler allows to create new polymeric materials with unique electrical properties. Li et al [7] prepared conducting shape memory polyurethane incorporating carbon black. They studied the shape memory properties by applying thermal heating but not electrical voltage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a portion of unrecoverable elongation, which is due to mechanical properties and relaxation of deformation for parent PU films used in the study. It has been reported [21] that almost complete recovery (up to 98%) can be reached in pure polyurethane. However, the presence of the conductive filler reduces the recovery rate down to 70% when the load is above the percolation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Deformation of the sample causes enhancement of the optical contrast due to interruption of the conductive layer with insulating PU micro-regions. The latter appear Table 1 Theoretical and experimental scaling exponents and fractal dimensions of the system depending on the dimensionality of embedding space, d or type of PU matrix modification with PANI Theoretical predictions [21] Experimental results bright on the images due to optical transparency of the PU elastomer. At 3 ¼ 0.65 PANI regions are still inter-connected and the sample looks electrically percolated, however, its electrical conductivity is about 10 times lower in comparison to the pristine sample.…”
Section: Resultsmentioning
confidence: 99%
“…In polyurethane/carbon black system containing 30 wt% of carbon black, the shape recovery ratio of the composite reduced from 98% to 65% [21]. It was also found that clay particles in polyurethane, reducing shape fixity ratio from 78% to 57% at 5 wt% of clay [22].…”
Section: Introductionmentioning
confidence: 99%